Irrigação com águas de níveis de salinidade diferentes aplicadas de acordo com a fase de desenvolvimento da mamoeira - Costa, Maria Eugênia da (2012)
The castor bean (Ricinus communis L.), due to its ability to produce satisfactorily under conditions of low rainfall is an alternative of great importance for the Brazilian semiarid region. Currently, however, has been stimulated their irrigated, since, in many cases, irrigation is the only way to ensure the production, mainly in tropical regions of hot, dry climate, which predominates in northeast Brazil. This experiment was conducted to evaluate the influence of irrigation with saline water on growth and yield of castor (BRS Energy), and monitor the evolution of some soil chemical properties along the crop cycle. The experimental design was randomized blocks with six treatments and five repetitions. The treatments consisted of combinations of phases of development of castor bean (vegetative and reproductive), and water salinities (0.55, 2.16, 3.53 dS m-1). Evaluations of growth (plant height, stem diameter and leaf number) were evaluated at 20, 40, 60, 80, 100 days after sowing. The soil samples were carried out concomitantly with the assessments of growth, the layers 0-0.10; 0.10 to 0.30, 0.30-0.50 m. The soil chemical properties were evaluated exchangeable sodium, exchangeable sodium percentage, electrical conductivity and pH. We also evaluated yield components, number and length of the racemes, number and weight of fruit, productivity and total productivity of the racemes. The results indicated that irrigation with saline water throughout the cycle of the castor bean productivity decreased approximately 26% compared with the water of low salinity. The adoption of management of water salinities increased sharply attributes Na +, PST and CE, but the conditions studied there was no negative impacts on the salinity / sodicity